2019
DOI: 10.1002/cphc.201900804
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Cyclic Voltammograms on Pt(111): Kinetics Simulations

Abstract: A detailed understanding of the electrochemistry of platinum electrodes is of great importance for the electrochemical oxidation of fuels and electrochemical reduction of dioxygen in fuel cells. The Pt(111) facet is the most representative model mimicking Pt nanoparticles and polycrystals for fundamental studies. Herein, we propose a site-specific model accompanied with the typical elementary steps of the electrochemistry of Pt (111) in non-adsorbing electrolyte within the potential range between 0.05 and 1.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…The assignment of the P2 and P3 peaks is controversial because of the complex adsorbate structure generated during the oxide formation. Computational simulations and ex situ X- 57,58 However, the simulations were performed considering acidic conditions. In alkaline solutions, the potentials and intensities of the P2 and P3 peaks of Pt(111) notably depend on the electrolyte cations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assignment of the P2 and P3 peaks is controversial because of the complex adsorbate structure generated during the oxide formation. Computational simulations and ex situ X- 57,58 However, the simulations were performed considering acidic conditions. In alkaline solutions, the potentials and intensities of the P2 and P3 peaks of Pt(111) notably depend on the electrolyte cations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The assignment of the P2 and P3 peaks is controversial because of the complex adsorbate structure generated during the oxide formation. Computational simulations and ex situ X-ray photoelectron spectroscopy (XPS) experiments suggested the stable coexistence of H 2 O ad , OH ad , or O ad on Pt surfaces due to simultaneous or sequential oxide formation. Simulations of voltammetric curves based on kinetic modeling indicated that the second anodic peak above 0.9 V corresponds to Pt–O ad (Pt–OH ad → Pt–O ad + H + + e – ) on several different adsorption sites, e.g., top, bridge, and hollow sites of Pt(111). , However, the simulations were performed considering acidic conditions. In alkaline solutions, the potentials and intensities of the P2 and P3 peaks of Pt(111) notably depend on the electrolyte cations. , The apparent separation of the P2 and P3 peaks in TMAOH compared to that in alkali metal hydroxides deserves particular attention.…”
Section: Resultsmentioning
confidence: 99%